Improving Learning Outcomes Of Islamic Cultural History Through The PBL In The Madrasah Aliyah Negeri Seram Barat - Hataul, Sukri; Hamka, Syamsuar (IAIN Ambon, 2024)
Education plays an important role in forming quality human resources. In the learning process, student motivation and involvement are crucial aspects that determine learning outcomes. The subject of Islamic Cultural History (SKI) is often considered a rote subject, making it less interesting for students. Therefore, innovative learning models are needed to increase students' understanding and motivation to learn. This research aims to improve the SKI learning outcomes of class The research method used was Classroom Action Research (PTK) which was carried out in two cycles. Each cycle consists of planning, action, observation and reflection stages. The research results show that the application of the PBL model can significantly improve student understanding and learning outcomes. In cycle I, the number of students who achieved the KKM increased compared to before the research, and in cycle II there was a more significant increase. This increase shows the effectiveness of the PBL model in improving student learning outcomes by encouraging them to be more active in learning, dare to express opinions, and be more independent in understanding the concepts being taught.